Peran Guru dalam Membimbing Konseling terhadap Siswa Kelas 6 SDIT Nurjali - Ira Restu Kurnia; Devia Haslihatul Latifah; Marchika Bella Mujwah; Nur Atika Safitri (Departement of Mathematics Education, 2024)
This study aims to determine the role of teachers in the implementation of counseling guidance. The role of teachers in the implementation of counseling guidance must be able to involve parties in the school such as students, subject teachers, principals and parents so that the counseling guidance program is carried out properly. Because many things or problems often arise in students when following the learning process at school. The role of teachers refered to in this study is the role of teachers as guides, counselors, informators, facilitators, mediators, collaborators, organizers, motivators, directors, initiators, transmitters, and evaluators in achieving educational success in schools. The method used is qualitative descriptive which aims to find out how the actual situation occurs and the actual phenomenon, then the researcher describes it into a research report. The result of the study is that teachers carry out their role in counseling guidance services in schools by applying a continuous, nuanced process, guiding with principles for all both male and female students, applying eastern culture, and effective and efficient implementation.